Single Leg Bridge Test is Not a Valid Clinical Tool to Assess Maximum Hamstring Strength - Gabriela Bissani Gasparin; João Breno Araujo Ribeiro-Alvares; Bruno Manfredini Baroni (North American Sports Medicine Institute, 2022)
# Background The single leg bridge test (SLBT) has been introduced in the sports context as a way of estimating hamstring muscle capacity for prevention and rehabilitation of hamstring strain injuries. # Purpose The primary aim was to examine the association between SLBT scores with concentric and eccentric knee flexor peak torques. Secondarily, this study aimed examine the association of between-limb asymmetries provided by SLBT and isokinetic tests. # Study design Cross-sectional study. # Methods One hundred male soccer players (20±3 years) performed the SLBT and the knee flexion-extension isokinetic dynamometry evaluation (60°/s) billaterally during a single visit. SLBT score (i.e., number of repetitions until failure) and concentric and eccentric knee flexor peak torques (normalized per body mass) were considered for analysis. For both SLBT and isokinetic dynamometry, between-limb asymmetry was calculated as the percentage difference between the left limb and the right limb. Associations were assessed through Pearson's correlation coefficient. # Results The mean SLBT score was 33.6±9.6 repetitions, concentric peak torque was 2.00±0.22 Nm/kg, and eccentric peak torque was 2.79±0.44 Nm/kg. Between-limb asymmetry was 0.4±9.6%, 1.08±8.5%, and 1.64±14.61% in SLBT, concentric, and eccentric tests, respectively. There was a poor association of SLBT score with concentric (p\<0.001, r=0.275) and eccentric (p=0.002, r=0.215) peak torques. The SLBT between-limb asymmetry was poorly associated with asymmetry found in concentric peak torque asymmetry (p=0.033, r=0.213) and was not associated with eccentric peak torque asymmetry (p=0.539, r=0.062). # Conclusion The SLBT should not be used as a clinical tool to assess the maximum strength of hamstring muscles. # Level of Evidence Level 3